Socialization of Using PASHA (Pain Assessment, Stimulation and Healing Application) as a Complementary Based of Pain Management - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola; Nurhamidah, Nurhamidah (CV. Media Digital Publikasi Indonesia, 2024)
Pain is one of the symptoms that is often found in any changes in body health. This PKM aims to provide the training to increase knowledge through socialization and outreach to the people at Campus and community in Bukittinggi. From this explanatory background, we conclude that using application is more effective to manage the pain. The purpose of implementing this PASHA is to help the pain problems with promotion methods by using complementary therapies on application. The method that has been used in this PKM includes scialization related to Complementary Based of Pain Management by using PASHA (Pain Assessment, Stimulation and Healing Application). The evaluation results showed a reduction in pain intensity by measuring the pain scale before and after being given pain management interventions through the PASHA (Pain Assessment, Stimulation and Healing) application. A measurement was use NRS and the average pain before and after is calculated. The results obtained were a decrease in the average pain before and after using PASHA. It is hoped that the campus and surrounding community will be able to continue the activities of using this application in pain management so that it can be used to improve the level of health in the community